Spindle Checkpoint Regulators in Insulin Signaling - Choi, Eunhee; Yu, Hongtao (Frontiers in Cell and Developmental Biology, 2018)
The spindle checkpoint ensures accurate chromosome segregation during mitosis and guards against aneuploidy. Insulin signaling governs metabolic homeostasis and cell growth, and its dysregulation leads to metabolic disorders, such as diabetes. These critical pathways have been extensively investigated, but a link between the two has not been established until recently. Our recent study reveals a critical role of spindle checkpoint regulators in insulin signaling and metabolic homeostasis through regulating endocytosis of the insulin receptor (IR). These findings have linked spindle checkpoint proteins to metabolic regulation, expanding the connection between cell division and metabolism. Here, we briefly review the unexpected roles of spindle checkpoint regulators in vesicle trafficking and insulin signaling.